10.A. Workshop: COVID19 immunisation passports – A golden solution or the golden apple of discord?. (30th September 2020) - ,; ,
Abstract: The COVID19 pandemic critically threatens global public health, development and sustainability. As a direct result, ideas, which would otherwise have never been considered, are being presented as golden solutions. One such case is that of the 'immunity passport', i.e. determining the movement of people within countries and across borders on the basis of their immunity status. The argument being made is that such a passport would allow people with immunity to help on the front line, as for example to alleviate pressure in hospitals safeguarding the health of many. Similar argumentation is used across sectors, with tremendous burden being placed on low-paid and seasonal workers, who may attempt to try and get infected to be 'able' to work or cross a border to seek work. Additionally, legislative provisions on testing for immunity expose individuals to enforced 'solutions' infringing upon their rights and privacy, and even stigmatising them. Thus, COVID19 represents a threat to human rights, individual freedoms and, ultimately, social cohesion, mostly impacting adversely vulnerable people already at a disadvantage. The legal nature of this measure raises questions on whether this is necessary and in accordance to a legitimate aim in a democratic society. Is there a difference between healthcare settings and the broader society? Who would manage 'immunity registries'? Could data safe and privacy safeguarded? Would human rights be infringed upon and with what implication for democracy? Vaccines are destined to become a catalyst in this debate. Currently, we do not know whether antibody presence translates to protection from subsequent infection, with uncertainty on antibody testing, response durability, and on the role of antibodies in conferring immunity. The same concerns are applicable to a future vaccine. Would it be acceptable to revisit the immunity passports in the advent of a vaccine? Where do we stand in terms of having a s! afe and effective vaccine? What is the role science can play to elucidate such dilemmas and inform policy? What role can patient summaries play were we to transition to recording immunity vs vaccination status? Immunity passports represent a Trojan horse to compromise democratic societies and exacerbate inequalities, also representing an impediment to empowerment. Safe care can be ensured by saying no to immunity passports and yes to citizen empowerment, with patient summaries associated with provenance and including immunization information for safe care. The principal objectives of the workshop are to a. examine assumptions and implications on immunity passports in a comprehensive manner, and b. inform on the need of evidence-informed dialogue to safeguard human rights, as well as global public health. Following four 10-min presentations, the Panel and the Chairs will enter a 20-min discussion. The audience will be able to respond to key propositions and ask questions through an interactive element. Key messages: Interdisciplinary scientific dialogue is key to assess proposed solutions and the implications thereof for evidence-informed policymaking safeguarding human rights and global public health alike. Threats to freedom, fairness and public health are inherent to any platform that is designed to segregate society on the basis of biological data. Social justice should guide all policies.